PENGARUH FINTECH DAN E-COMMERCE TERHADAP KEPUASAN KEUANGAN PADA PELAKU UMKM - Ivan Permana; Dewi Widyaningsih; Afiza Regita Cahyani (LPPM Politeknik Pratama, 2021)
This study aims to see how much influence the financial technology variable with the e-commerce variable has on the financial satisfaction variable in the city of Salatiga, Central Java province. Data collection was carried out for one month using Googleform to find out answers related to research variables and respondent biodata. Respondents consist of SMEs in the city of Salatiga with a total of 100 respondents. The assessment of the answers to the questionnaire uses a Likert scale. The data analysis method used multiple linear regression assisted by SPSS 23 software to process it. The final result shows that financial technology and e-commerce variables have a significant influence on financial satisfaction. The e-commerce variable is the most dominant in achieving optimal financial satisfaction for respondents.